Structural performance evaluation of hybrid polymer composites for critical infrastructure pick-and-place robot grippers using silica nanoparticles - Mani, Megavannan; Murgaiyan, Thiyagu; Krishnan, Pradeep Kumar (International journal of structural integrity, 2023)
PurposeThis study focuses on the structural performance assessment of hybrid polymer composites for pick-and-place robot grippers used in critical infrastructure. This research involved the creation of composite materials with different nanoparticle concentrations, followed by extensive testing to assess the mechanical properties of the materials, such as strength, stiffness and durability.Design/methodology/approachThe composites comprised bidirectional interply inclined carbon fibers (C), S-glass fibers (SG), E-glass (EG), an epoxy matrix and silica nanoparticles (SNiPs). During construction, the composite materials must be carefully layered using quasi-static sequence techniques (45°C1/45°SG2/45°EG2/45°C1/45°EG2/45°SG2/45°C1) to obtain the epoxy matrix reinforcement and bonding using 0, 2, 4 and 6 wt. % of silica nanoparticles.FindingsAccording to various test findings, the 4 wt. % of SNiPs added to polymer plates exhibits the maximum strength outcomes. The average results of the tensile and flexural tests for the polymer composite plates with 4 wt. % addition SNiPs were 127.103 MPa and 223.145 MPa, respectively. The average results of the tensile and flexural tests for the plates with 0 wt.% SNiPs were 115.457 MPa and 207.316 MPa, respectively.Originality/valueThe authors hereby attest that the research paper they have submitted is the result of their own independent and unique labor. All of the sources from which the thoughts and passages were derived have been properly credited. The work has not been submitted for publication anywhere and is devoid of any instances of plagiarism.Highlights The study enhances the engineering materials for innovative applications.The study explores the mechanical behavior of carbon/S-glass/E-glass fiber composites.Silica nanoparticles were enhancing mechanical characteristics of the composite structure.